Electrospin-coating of nitrocellulose membrane enhances sensitivity in nucleic acid-based lateral flow assay - Yew, Chee Hong; Azari, Pedram; Choi, Jane Ru; Li, Fei; Pingguan-Murphy, Belinda (Elsevier, 2018)
Point-of-care biosensors are important tools developed to aid medical diagnosis and testing, food safety and environmental monitoring. Paper-based biosensors, especially nucleic acid-based lateral flow assays (LFA), are affordable, simple to produce and easy to use in remote settings. However, the sensitivity of such assays to infectious diseases has always been a restrictive challenge. Here, we have successfully electrospun polycaprolactone (PCL) on nitrocellulose (NC) membrane to form a hydrophobic coating to reduce the flow rate and increase the interaction rate between the targets and gold nanoparticles-detecting probes conjugates, resulting in the binding of more complexes to the capture probes. With this approach, the sensitivity of the PCL electrospin-coated test strip has been increased by approximately ten-fold as compared to the unmodified test strip. As a proof of concept, this approach holds great potential for sensitive detection of targets at point-of-care testing.